Corporate Social Responsibility ( CSR) Practices in India: A Comparative Study of the Most Profitable Private Sector Banks, Public Sector Banks & Non-Banking Financial Companies (NBFCs) (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2024)
A business cannot flourish unless and until it takes care of its environment, its society and its  people. It has an obligation to deliver goods and services in such a way that it does not harm the  environment or its stakeholders and thus has customer and society's welfare as its goal and not  mere maximisation of profits. People will lose confidence in an organisation which is harming the  country's resources or not working for the best interests of its stakeholders as was identified by  (Norwal & Sharma, 2006) who discussed that crisis is the real test of capabilities and socially  responsible companies are perceived differently by people. Thus, companies who are serving the  society well, will be able to persist in the long run while the others may even end up losing their  competitive advantage. This concept is no less important for financial firms. Financial companies  like Banks and Non-Banking Financial Companies (NBFCs) play an important role in meeting the  funding requirements of other firms and acts as a mediator of funds from the one who have funds  to the ones who need funds. A financial firm engaged in serving the society will have a positive  image and will be able to retain its customers even in the times of financial crisis. The purpose of  study is to shed light on the Corporate Social Responsibility (CSR) practices discharged by most  profitable Public Sector Banks, Private Sector Banks and NBFCs in India and their comparison as  to their contribution towards CSR activities. It was found that Private Sector Banks and NBFCs are  more active as to its contribution towards CSR and it corresponds to its better performance.
Keywords: corporate social responsibility; crisis; stakeholders; profitability; financial firms